Life in the Polar Winter - Strategies of Survival - de Korte, J.; Hacquebord, L.; Prins, H.H.T. (ARCTIC, 1991)
The perception of the polar winter as a period in which organisms have to struggle for survival is common among people living almost exclusively outside the polar regions, even if sometimes in areas with winter resembling the polar winter. . For arctic organisms, endemic to and wintering in the far North, the polar winter possibly has a different significance. For these organisms it is often a period of rest, during which they conserve energy and prepare for reproduction in the coming feeding season. Until the last decades of this century, we knew little about the significance of the polar winter for organisms that live there year-round. For migratory species it is obviously a rather intolerable season, but how resident species survive and live through the winter was unknown. . The series of eight papers presented here . stem from a multidisciplinary symposium organized by the Arctic Centre of the University of Groningen on the occasion of the 375th anniversary of this university of 1989. . The guiding question of this symposium was: How do humans and their living resources survive the polar winter? As the resources are both terrestrial and marine, both are discussed when presenting organisms from different trophic levels. . This series of papers concludes with a study of the successes and misfortunes of western Europeans wintering in the High Arctic in the 16th and 17th centuries and an article about Russian trappers during the 18th and 19th centuries wintering in Spitsburgen. .